Efektivitas Brain Based Learning Berbantuan LiveWorksheets Berbasis Realistic Mathematics Education terhadap Kemampuan Pemecahan Masalah - Adellia Aristawati; Zuida Ratih Hendrastuti; Paskalia Pradanti (Universitas Muhammadiyah Semarang, 2025)
This research was initiated due to the low level of students’ problem solving abilities at SMP Negeri 3 Mertoyudan. Learning was still teacher-centered and the learning media used were not interactive. The purpose of this study is to examine the effectiveness of the Brain Based Learning model assisted by LiveWorksheets based on Realistic Mathematics Education compared to conventional models and to examine the improvement in problem-solving ability after the implementation of the model. The study applied a quantitative approach through a quasi-experimental nonequivalent pretest-posttest control group design. The research subjects were selected using a cluster random sampling techniques, namely class 7B as the control class and class 7D as the experimental class. The data were collected through observation, interviews, tests, and documentation, with instruments such as observation forms, interview guides, and test. Data analysis was conducted using prerequisite tests (normality and homogeneity tests) and hypothesis testing: hypothesis 1 (independent sample t-test) and hypothesis 2 (paired sample t-test and N-Gain). The findings indicated that the Brain Based Learning model assisted by RME-based LiveWorksheets, proved to be more effective than the conventional model () and contributed to the enhancement of students’ problem -solving abilities.